2019
DOI: 10.1371/journal.pone.0209365
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of varicella-zoster virus infection in patients with breast cancer after adjuvant radiotherapy: A population-based cohort study

Abstract: Background/PurposeLimited evidence has been obtained on varicella-zoster virus (VZV) infection in patients with breast cancer as a complication related to adjuvant radiotherapy. We conducted a cohort study aimed to assess the risk of VZV infection in this patient setting.Materials and methodsWe used the National Health Insurance Research Database to identify 65,981 patients with breast cancer in Taiwan who underwent breast surgery between 2000 and 2011. After a 1:1 propensity score match was obtained between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Concerning the herpes zoster presented 2 months later, we think that it was favored by immunosuppression induced by the general steroid therapy. However, we cannot eliminate with certainty that it was not induced by radiotherapy as suggested in several articles (34,34).…”
Section: Discussionmentioning
confidence: 86%
“…Concerning the herpes zoster presented 2 months later, we think that it was favored by immunosuppression induced by the general steroid therapy. However, we cannot eliminate with certainty that it was not induced by radiotherapy as suggested in several articles (34,34).…”
Section: Discussionmentioning
confidence: 86%
“…In a retrospective case series, 8.1% of patients with small‐cell lung cancer developed HZ after intensive treatment that included RT; these events frequently occurred within 1 year after the initiation of treatment 22 . In a large matched‐pair study, patients who received postoperative RT for breast cancer exhibited a 1.51‐fold higher risk of HZ than non‐RT controls; this elevated risk was observed within 5 months of RT completion 20 . A prospective cohort study investigated HZ incidence before and after a diagnosis of cancer, and the results indicated a greater risk of HZ among chemotherapy recipients who had solid organ malignancy compared with noncancer population controls (adjusted HR, 1.84; 95% CI, 1.54‐2.20) and a moderately greater risk among RT recipients (adjusted HR, 1.38; 95% CI, 1.17‐1.63) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1940s, several studies have investigated the development of HZ after radiation therapy (RT) and have described the frequency and timing of events and the clinical course; however, most of those studies were limited to cohorts of patients with a specific malignant disease and lacked robust statistical analyses 19‐24 . Some epidemiological studies investigated HZ incidence among patients with cancer and measured the effects of anticancer therapy 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Nouri, it was reported in patients who was treated with arsenic trioxide, VZV can reactivate and contribute myeloma and colon cancer [32]. Yo-Liang Lai declared, there was an increase in the risk of varicella-zoster virus infection in patients, suffering from breast cancer after adjuvant radiotherapy [35]. However some studies claimed VZV is able to cause Inflammatory bowel disease (IBD), or more severe disease in colon.…”
Section: Discussionmentioning
confidence: 99%